Role of B-Cell in the Pathogenesis of Systemic Sclerosis - Thoreau, Benjamin; Chaigne, Benjamin; Mouthon, Luc (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is a rare multisystem autoimmune disease, characterized by fibrosis, vasculopathy and autoimmunity. Recent advances highlighted the significant implication of B-cell in SSc. B-cell is present in affected organs, its subpopulations are disrupted, and displays an activated phenotype, and the regulatory capacities of B-cells are impaired as illustrated through the decrease of the IL-10+ producing B-cell subpopulation or the inhibitory membrane co-receptors density. Recent multi-omics evidences highlight the role of B-cell mainly in the early stage of SSc, and preferentially during severe organ involvement. This dysregulated homeostasis explains partly the synthesis of anti-endothelial cells autoantibodies (AECA) or anti-fibroblast autoantibodies (AFA), proinflammatory or profibrotic cytokines (interleukin-6 and transforming growth factor-β) produced by B-cells and plasma cells. That is associated with cell to cell interactions with endothelial cells, fibroblasts, vascular smooth muscle cells and other immune cells, altogether leading to cells activation and proliferation, cell resistance to the apoptosis, the impairment of regulatory mechanisms, and cause fibrosis of several organs encountered in the SSc. Finally, alongside these exploratory data, treatments targeting B-cells, through their depletion by cytotoxicity (anti-CD20 monoclonal antibody), or the cytokines produced by the B-cell, or their costimulation molecules seem interesting, probably in certain profiles of early patients with severe organic damage.